Ex-situ propagation of Pogostemon helferi (Hook. f.) Press using tissue culture and a hydroponics system - Wangwibulkit, Maneerat; Vajrodaya, Srunya (Agriculture and Natural Resources, 2016)
Pogostemon helferi (Hook. f.) Press, locally known as “dao-noi” is a rare Thai indigenous aquatic plant that is popular for use in aquaria and water gardens. To address its scarcity and to make the plant more readily available, two experiments were conducted to find the optimum conditions for ex-situ propagation. The first experiment aimed to determine the concentration of growth regulators for its micropropagation. Sterile explants were cultured using a combination of 3-indoleacetic acid (IAA) and 6- benzylaminopurine (BA) supplements in Murashige and Skoog media (MS). MS media containing IAA 0.1 mg/L and BA 3 mg/L induced the highest percentage of callus formation (93.33%). In addition, MS media with IAA added at 0.3 mg/L significantly (p < 0.05) increased the number of new shoots appearing and their length after 8 wk. The second experiment aimed to determine the optimum electrical conductivity of the nutrient solution and the humidity level for P. helferi growth within a hydroponics system. The results showed that an electrical conductivity of 1.6 mS/cm and 80% humidity were optimal for P. helferi growth and production to a marketable size. These methods should enable the production of P. helferi appropriate to support market demand and thus can reduce the current practice of harvesting wild plants in their natural habitat.